Analisis Sikap Multikultural Siswa Di SD 1 Rahtawu Kecamatan Gebog Kudus - Ummi Bunga Aditya; Mohammad Syaffruddin Kuryanto; Muhammad Noor Ahsin (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study was to analyze the multicultural attitudes of students at SD 1 Rahtawu. This research is a descriptive qualitative research aproach. The subjects of this study were 3 students from grade 4 and 4 students from grade 6. The instruments used in this study were interviews, observations, and incidental notes. The validity of the data used source triangulation, technical triangulation and time triangulation. Data analysis uses an interactive model according to Miles and Huberman, namely data reduction, data display and conclusion drawing. The results of the study show that students' multicultural attitudes include tolerance, respect for opinions, being open, having knowledge about the diversity of Rahtawu Village and having an attitude of interdependence with each other. This attitude is shown by most of the students at SD 1 Rahtawu. The habit of students living side by side with their friends who have different religious and cultural backgrounds makes students understand and understand the importance of loving cultural and religious diversity, especially in the school environment.